Immigrants and Immigration Policy in Ageing Finland - Łobodzińska, Anna (Bulletin of Geography. Socio-economic Series, 2011)
The paper addresses the issue of current immigration to Finland in the context of population ageing. It is estimated that about 40% of the present labour force will have withdrawn from the Finnish labour market by the year 2020. The government of this rapidly ageing country is seeking possible remedies to the problem of a shrinking labour force. The necessity of attracting a new workforce as well as the growing number of immigrants in the ethnically homogeneous Finnish society create a need for more detailed and creative immigration policy. The paper analyzes the age and economic structure of the immigrant population, its participation in the labour market as well as the importance of immigration in contemporary demographic changes in Finland. Another aim of this paper is to outline major issues concerning Finnish immigration policy.